2011
DOI: 10.1177/070674371105600108
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorder in Detained Male Adolescents as Risk Factor for Serious Recidivism

Abstract: Objective: A growing body of research consistently shows that detained minors bear substantial mental health needs. However, the relation between mental disorder and criminal recidivism has largely remained unexplored. Our study examines whether psychiatric disorders increase the likelihood of recidivism after controlling for time at risk, criminal history, and the presence of other disorders. Method: Participants (n = 232) were detained male adolescents from all 3 youth detention centres in Flanders, Belgium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 28 publications
2
52
0
7
Order By: Relevance
“…We did not measure rates of childhood emotional and sexual abuse in this study, which is an area for future research. Around one-fifth of the detained sample had a lifetime SUD, which is at the lowest end of estimates reported in the studies of juveniles in custody in Western countries (Colins et al, 2011). Such disorders are potentially treatable, and the findings of the current survey suggest that treatment services for substance abuse in juvenile detention facilities should be prioritized.…”
Section: Discussionmentioning
confidence: 78%
“…We did not measure rates of childhood emotional and sexual abuse in this study, which is an area for future research. Around one-fifth of the detained sample had a lifetime SUD, which is at the lowest end of estimates reported in the studies of juveniles in custody in Western countries (Colins et al, 2011). Such disorders are potentially treatable, and the findings of the current survey suggest that treatment services for substance abuse in juvenile detention facilities should be prioritized.…”
Section: Discussionmentioning
confidence: 78%
“…People with substance abuse in particular are reported to have a higher risk of re-incarceration, especially when they have a cooccurring severe mental illness (Baillargeon et al, 2010;Colins et al, 2011). This may depend on substance abusers' being more likely to engage in drug-defined and drug-related offences after release from prison.…”
Section: Mental Disorders and Risk Of Re-incarcerationmentioning
confidence: 93%
“…However, this study used broad diagnostic grouping categories and did not investigate individual psychiatric disorders. Other studies have also reported that psychiatric comorbidity predicted criminal repeat offending, but there was no information regarding which psychiatric comorbidity combination contributed to these results [22, 26]. …”
Section: Introductionmentioning
confidence: 99%